Adapting of Quality Education; Towards Excellent and Competitive Higher Education - Junaidah, Junaidah (JURNAL AL-TANZIM, 2022)
This study aims to analyze the adaptation of higher education in facing the dynamics of the times so that excellence and being able to win the competition. This study uses a phenomenological type of qualitative approach, in which researchers collect data through interviews, observation, and documentation. The data analysis technique is carried out through condensation, display, and data verification stages. The results showed that Raden Intan State Islamic University of Lampung has various strategies in improving the quality of its education through vision, leadership, and managerial reformulation, promoting good service, which is the institution's core business, both in academic and non-academic fields. Need learning-based services are also carried out in the form of e-learning-based learning, high impact-based lecturer research, community service, financial management, human resources, information systems, organizational culture, and collaboration, both in academic and non-academic fields.